2019
DOI: 10.3390/su11102939
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Enterprise Risk Management in Sustainable Decision-Making: A Cross-Cultural Comparison

Abstract: The goal of this paper is to examine how cultural differences moderate the effectiveness of an organization’s enterprise risk management (ERM) program in sustainable decision-making. Using an experimental design, this study found that Chinese participants, characterized by a stronger prevention focus, were more proactive in mitigating environmental, social and governance (ESG)-related risks under a loss-framed risk management philosophy, whereas American participants, characterized by a stronger promotion focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 74 publications
(150 reference statements)
1
10
0
Order By: Relevance
“…The impact of cultural factors on ERM adoption. There is a pilot work of Liu (2019) who analyzed this aspect in a cross-cultural context of China and the US, acknowledging the importance of cultural factors. However, this stream of research is new, and more research is welcomed, for example, on the impact of culture on different components of ERM.…”
mentioning
confidence: 99%
“…The impact of cultural factors on ERM adoption. There is a pilot work of Liu (2019) who analyzed this aspect in a cross-cultural context of China and the US, acknowledging the importance of cultural factors. However, this stream of research is new, and more research is welcomed, for example, on the impact of culture on different components of ERM.…”
mentioning
confidence: 99%
“…In this first research, it was not included since following the principles defined by the ISO 31.000:2018, the risk management has to be tailored to each organization [5], and it implies that each one establishes its own assessment criteria. It would be very interesting if this evaluation were carried out on different Western countries operating in China, to contrast with previous studies on how culture influences risk assessment [64,73].…”
Section: Discussionmentioning
confidence: 99%
“…Liu [73] examined how cultural differences moderate the effectiveness of an organization's enterprise risk management (ERM) program in sustainable decision making. She found that Chinese participants were characterized by a stronger prevention focus, whereas American participants were characterized by a stronger promotion focus.…”
Section: Risk Perception Considering the Cultural Approachmentioning
confidence: 99%
“…In order to reduce the risk of medical errors, operators invest in employee functional training, as the risk of medical errors affects the interaction of other risks, such as strategic risks, financial risks, and operational risks, which can affect the overall risk of the organization, as well as the sustainable development of the company (Liu 2019). Therefore, in financial management planning, an enterprise that invests in functional training can strengthen the functional ability of medical professionals (Senior 2017), improve the quality of professional personnel and medical quality, eliminate potential medical risks, and reduce the financial losses of the enterprise (Carver and Hipskind 2019).…”
Section: Literature Reviewmentioning
confidence: 99%